Characterization of physical properties of binary system of erythromycin stearate-sodium starch glycolate by compression force effect - Setyawan, Dwi; Sumirtapura, Yeyet C; Soewandh, Sundani N; Tj, Daryono Hadi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Characterizations of the physical properties of binary system of erythromycin stearate (ERS)-sodium starch glycolate(SSG) due to compression force, had been carried out. The solid state properties were evaluated by powder X-ray diffraction (PXRD), scanning electron microscope (SEM) and differential thermal analysis (DTA) methods. The weight fraction of mixtures ERS: SSG (90:10), (80:20) and (70:30) were compressed using hydraulic press and flat plain punches with a diameter of 13 mm. The compression force was 29.5 kN. Diffraction peaks at 2θ = 5.6; 10,6 and 25.6° were used to determine the full width at half maximum (FWHM), crystallite size and preferred orientation. Peak broadening was calculated by measuring the FWHM. FWHM values, crystallite size and preferred orientation of the crystallites were calculated by WinPlotr program. The results of the study showed that the FWHM value increased at all the crystal lattice as the fraction of SSG increased. The crystallite size and peak intensity decreased gradually as fraction of SSG increased. Scanning Electron Microscope (SEM) analysis indicated that SSG was dispersed on surface and inside of the tablet of ERS at all combination. The phase diagram of binary system ERS and SSG showed a no interaction of ERS and SSG.Key words : characterization, physical properties, ERS, SSG, compression force